The Effect of Problem-Based Learning Models on Students' Science Process Skills and Critical Thinking Skills SDN 10 Sidomulio Sei Balai Regency Batu Bara - Sri Ramadani; Hasratuddin Hasratuddin; Isti Rokhiyah (Universitas Muhammadiyah Enrekang, 2025)
The study aims to analyze the differences in the influence of problem-based learning models with conventional learning on students' science process skills, analyze the differences in the influence of problem-based learning models with conventional learning on students' critical thinking skills, analyze the interaction between learning and students' initial abilities on students' science process skills, and analyze the interaction between learning and students' initial abilities on students' critical thinking skills at SD Negeri 10 Sidomulio Sei Balai, Batu Bara Regency. The research method is an experiment with a 2x3 ANOVA design. The study population was fourth-grade students at SD Negeri 10 Sidomulio Sei Balai, Batu Bara Regency. The research sample was determined using a cluster random sampling technique so that a sample of 56 students was obtained. Data collection techniques were tests and non-tests. The instruments used were tests of students' science process skills and critical thinking skills in science. The data analysis technique was ANOVA (Analysis of Variance) by comparing the learning outcomes of students in each class. The results of the study concluded that there were differences in students' science process skills using the PBL learning model with students' science process skills using conventional learning. There were differences in students' critical thinking skills using the PBL learning model with students' critical thinking skills using conventional learning. There is an interaction between learning and prior abilities on students' science process skills. There is an interaction between learning and prior abilities on students' critical thinking skills.